Fecal Incontinence Causes, Management and Outcome - Catto-Smith, Anthony G. (IntechOpen, 2014)
Fecal incontinence is a common and disabling condition that unfortunately remains an "orphan" in terms of medical research and effective therapies. This book provides a brief review of the pathophysiology of fecal incontinence with specific focus on women and children. Authorship is drawn internationally, with a strong surgical input. Contributions from the authors provide critical reviews of the evaluation of function, with illustrations of a range of surgical interventions which might be applied should medical therapies fail.